2021
DOI: 10.1590/1413-81232021269.07412020
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência e coocorrência de Experiências Adversas na Infância: um inquérito de base escolar no município do Rio de Janeiro

Abstract: Resumo Este estudo tem como objetivos estimar a prevalência de Experiências Adversas na Infância (EAI), investigar o seu perfil de coocorrência e sua distribuição de acordo com características individuais, familiares, socioeconômicas e escolares de adolescentes de escolas públicas e privadas de uma Região Administrativa do Rio de Janeiro. Trata-se de um estudo seccional com 681 indivíduos, selecionados através de amostragem aleatória complexa. As EAI foram identificadas através do questionário QUESI e pergunta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 51 publications
0
4
0
6
Order By: Relevance
“…It is worth noting that separations of couples usually involve periods of intense and prolonged stress, with emotional and financial repercussions on the family and the child itself. This finding is corroborated by a study that showed a trend towards an increase in the number of ACEs in environments where children did not live with both parents, favoring the experience of emotional neglect and physical abuse, in addition to compromising child development by reducing child protection, family income and emotional security 7 .…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…It is worth noting that separations of couples usually involve periods of intense and prolonged stress, with emotional and financial repercussions on the family and the child itself. This finding is corroborated by a study that showed a trend towards an increase in the number of ACEs in environments where children did not live with both parents, favoring the experience of emotional neglect and physical abuse, in addition to compromising child development by reducing child protection, family income and emotional security 7 .…”
Section: Discussionmentioning
confidence: 57%
“…Older mothers, on the other hand, often do not even have the support of the child's own father. A study in the state of Rio de Janeiro showed that in cases where the mother had her child in the limit age groups (below 20 and above 35), physical neglect and abuse were more common 7 . Additionally, another study in a hospital in the state of Amazon, in turn, observed that younger mothers tend to exercise their parenting more continuously, showing greater availability in their daily lives, perhaps due to the inexistence of a formal job 23 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A fim de se entender os impactos no desenvolvimento infantil causados pela violência, é importante conhecer as mais diversas formas em que ela ocorre. A leitura realizada evidenciou o fato de a violência em questão ainda ser um tema estranho para boa parte dos brasileiros, os Além dessas definições, a revisão de Stochero (2019) traz outra forma de se classificar as Experiências Adversas na Infância (EAI) ao apresentar os conceitos de experiências de ameaça ou de privação. Experiência de ameaça são aquelas que representam riscos à integridade física das vítimas, enquanto as de privação consistem na ausência de estímulos ambientais esperados, tais como cuidado e afeto dos genitores.…”
Section: Caracterização Da Violência Contra Crianças E Adolescentesunclassified